A Numerical Approach for Solving Nonlinear Singularly Perturbed Boundary Value Problem Arising in Control Theory - Kumar, P. Murali Mohan; Kanth, A. S. V. Ravi (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, a numerical approach based on non-iterative integration method with a small deviating argument for nonlinear singularly perturbed two point boundary value problems is discussed. The technique of quasilinearization is used to linearize nonlinear singular perturbation problem into a set of linear singularly perturbed equations. The continuous problem is replaced by an approximate first order differential equation with a delay argument which is non-iterative and then the application of numerical integration method to achieve a recurrence relationship of three terms. To demonstrate the effectiveness the proposed method are experimented with nonlinear problems.